Evaluation of Four Indigenous Non-Saccharomyces Yeasts Isolated from the Shangri-La Wine Region (China) for Their Fermentation Performances and Aroma Compositions in Synthetic Grape Juice Fermentation - Yue Zhao; Qingyang Sun; Bin Tian; Shusheng Zhu; Fei Du; Ruzhi Mao; Su Li; Lijing Liu; Yifan Zhu (Journal of Fungi, 2022)
This study investigated the fermentation performances and aroma compositions of synthetic grape juice that was fermented by four indigenous non-Saccharomyces yeast isolates that were obtained from the Shangri-La wine region (China): Meyerozyma guilliermondii (AD-58), Saccharomycopsis vini (BZL-28), Saturnispora diversa (BZL-11), and Wickerhamomyces anomalus (DR-110), in comparison to those of Saccharomyces cerevisiae (EC1118). The four indigenous non-Saccharomyces yeasts showed a lower fermentative capacity and a lower conversion rate of sugar to alcohol, but a higher yield of volatile acidity. W. anomalus (DR-110) had a greater ability to produce numerous esters and short-chain fatty acids and the representative flavors of its fermented medium were fruity and fatty. Sac.vini (BZL-28), interestingly, exhibited great capacity in the formation of many monoterpenes, particularly (Z)-β-ocimene, E-β-ocimene, linalool, citral, and geraniol and its fermented medium was characterized by a strong fruity (citrus-like) and floral flavor. M. guilliermondii (AD-58) and Sat. diversa (BZL-11) only mildly affected the aroma profiles of their resultant fermented media, since the concentrations of most of the volatiles that were produced by these two isolates were much lower than their sensory thresholds. The four indigenous non-Saccharomyces yeasts exhibited distinctive fermentation performances and aroma production behaviors. In particularly, W. anomalus (DR-110) and Sac. vini (BZL-28) have shown good potential in enhancing the aromas and complexity of wine.